O ENSINO DA LEITURA E A PERSPECTIVA DISCURSIVA DE LINGUAGEM: Implicações para a formação leitora de crianças do 2º ano do ensino fundamental - VIEIRA, Edilene de Jesus Furtado Ferreira (2024)
This research is part of the professional master's degree, of the Postgraduate Program in Basic Education Teaching Management, at the Federal University of Maranhão – UFMA. It develops from the following problematizing question: what assumptions from the discursive perspective of language can support the organization of reading teaching situations in 2nd year elementary school classes in a municipal school in Raposa-MA? We define as a general objective: to understand, from the discursive perspective of language, assumptions to support the organization of reading teaching situations in 2nd year elementary school classes, materialized, through a book of teaching narratives, guiding pedagogical practice in this context. As specific objectives, we define: situate the conceptions of language, reading and text, situating the process of teaching reading from the discursive conception of language; highlight the conceptions of language, reading and text of the collaborating teachers and how they relate to the practices of teaching reading in the classroom; identify the possibilities and challenges for organizing reading teaching practices based on the relationships between the discursive conception of language and the guidelines of official curricular documents (BNCC and DCTMA); produce, based on the assumptions of the discursive conception of language, a book of teaching narratives to support the process of teaching reading in 2nd year elementary school classes at a municipal school in Raposa-MA. Regarding the methodological path, the research was organized as follows: in terms of nature, as intervention research in education. The approach is qualitative and the procedures are based on collaborative action research. This research is anchored in some theoretical assumptions of Bakhtin/Volochinov (2006), to understand the discursive and dialogic process of language. Regarding reading practices, we dialogue with the primary sources of studies by Bajard (2021), Curto, Morillo and Teixidó (2000), Geraldi (2011), Jolibert (1994, 2006) and Smolka (1988). Other secondary sources are mobilized to analyze the object in question. Our findings indicate that the discursive conception of language presents specific perspectives for the constitution of reading teaching practices as a process of understanding texts, for a contextualized teaching in which the child learns by attributing meaning to written language since the work takes place in the classroom class considering texts in their real contexts of production and their social uses. In turn, the child learns to develop their human capabilities and reading is a fundamental cultural instrument for this process. To this end, the educational product created from this dissertation aims to contribute to teaching practice, for teaching reading, based on this conception of language.